1999
DOI: 10.1073/pnas.96.3.840
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the ternary complex of human 17β-hydroxysteroid dehydrogenase type 1 with 3-hydroxyestra-1,3,5,7-tetraen-17-one (equilin) and NADP +

Abstract: Excess 17␤-estradiol (E 2 ), the most potent of human estrogens, is known to act as a stimulus for the growth of breast tumors. Human estrogenic 17␤-hydroxysteroid dehydrogenase type 1 (17␤-HSD1), which catalyzes the reduction of inactive estrone (E 1 ) to the active 17␤-estradiol in breast tissues, is a key enzyme responsible for elevated levels of E 2 in breast tumor tissues. We present here the structure of the ternary complex of 17␤-HSD1 with the cofactor NADP ؉ and 3-hydroxyestra-1,3,5,7-tetraen-17-one (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 42 publications
9
88
1
Order By: Relevance
“…The structure of Equilin 2, was determined by Sawicki et al (1999b), who demonstrated that the presence of the unsaturated C7-C8 bond in the B ring rotates the C and D rings of the steroid such that the 17-keto oxygen atom, O17, is translated by 0.73 Å with respect to the analogous oxygen atom of 3 when an overlay of the two structures was performed based on the superposition of the A rings. The translation of the oxygen atom was implicated in the increased anti-human estrogenic 17-hydroxysteroid dehydrogenase 1 (17-HSD1) inhibitory behaviour of 2 with respect to 17-estone 3 (Sawicki et al, 1999a). The impact of the inhibitory behaviour of 2 is that it causes a reduction of the active estrogen, 17-estradiol, which is present in elevated concentrations in human breast tumour tissues and responsible for the accelerated growth of the tumour tissue.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The structure of Equilin 2, was determined by Sawicki et al (1999b), who demonstrated that the presence of the unsaturated C7-C8 bond in the B ring rotates the C and D rings of the steroid such that the 17-keto oxygen atom, O17, is translated by 0.73 Å with respect to the analogous oxygen atom of 3 when an overlay of the two structures was performed based on the superposition of the A rings. The translation of the oxygen atom was implicated in the increased anti-human estrogenic 17-hydroxysteroid dehydrogenase 1 (17-HSD1) inhibitory behaviour of 2 with respect to 17-estone 3 (Sawicki et al, 1999a). The impact of the inhibitory behaviour of 2 is that it causes a reduction of the active estrogen, 17-estradiol, which is present in elevated concentrations in human breast tumour tissues and responsible for the accelerated growth of the tumour tissue.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Later, equilin (Fig. 3e), an equine oestrogen that is a major component of Premarin, used in hormone replacement therapy, was also shown to inhibit 17b-HSD1 (IC 50 !1 mM), and the crystal structure of the 17b-HSD1 homodimer in a ternary complex with NADP C and equilin was solved (Sawicki et al 1999). Equilin binds at the substrate binding site, with the substrate entry loop in a closed conformation.…”
Section: Inhibitors Of 17b-hsd1mentioning
confidence: 99%
“…The surface of the tunnel is complementary to the C 18 steroidal scaffold and ensures selectivity towards estrogenic substrates 26 . At the C-terminal recognition end, hydrophilic amino acids form hydrogen-bonds to the 3-hydroxy group of the substrate 27,28 .…”
Section: B-hsd1 Inhibitionmentioning
confidence: 99%